The Investigation of Cryptosporidium spp. Prevalence in Cattle and Farmers by ELISA - ÖZÇELİK, SEMRA; ÖZÇELİK, SEMRA; POYRAZ, ÖMER; KALKAN, KADİR; MALATYALI, ERDOĞAN; DEĞERLİ, SERPİL (My University, 2012)
Cryptosporidium spp. is an important cause of enteritis for animals and humans. As the parasite has zoonotic potential, it is aimed to investigate the prevalence in people who had close contact with livestock, in control group who lived in Centrum and cattle. Fecal samples collected from 50 farmers who lived in different villages of Sivas and 65 people to be control group lived in Sivas Center without gastrointestinal discomfort and 200 cattle and calf breeding different county during the period from September 2009 to September 2010. Fecal samples were stored in 10% formalin until examination and then studied with Cryptosporidium Stool Antigen Microwell ELISA Kit. As a result, positive rate were found 4(6.2%) in control group and 9(18%) in study group, (chi(2)=3.95, P<0.05). On the other hand, 15 (7.5%) of the cattle and calve samples gave positive reaction with Cryptosporidium spp. ELISA.